Incidence and Risk Factors of Hepatic Fibrosis in Psoriatic Patients Receiving Methotrexate with Concomitant Acitretin Therapy and Methotrexate Monotherapy - Rattanakaemakorn P; Pinyowiwat P; Iamsumang W; Chanprapaph K; Suchonwanit P (Dove Medical Press, 2021)
Ploysyne Rattanakaemakorn, Prinpat Pinyowiwat, Wimolsiri Iamsumang, Kumutnart Chanprapaph, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat Suchonwanit; Kumutnart ChanprapaphDivision of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, ThailandTel +66-2-2011141Fax +66-2-201-1211 ext 4Email poonkiat@hotmail.com; kumutnartp@hotmail.comBackground: The use of methotrexate-acitretin (MTX-ACI) combination therapy in treating psoriasis has been limited due to concerns related to hepatic fibrosis. However, in vitro evidence revealed a protective effect of acitretin in methotrexate (MTX)-induced liver fibrosis.Objective: This study aimed to compare the real-life incidence of hepatic fibrosis in patients with psoriasis receiving MTX-ACI and MTX monotherapy and to investigate factors associated with hepatic fibrosis in MTX-exposed patients.Methods: A retrospective cohort study was conducted based on a real-life registry containing data on patients with psoriasis who were administered MTX-ACI or MTX between 2008 and 2019 and underwent transient elastography according to cumulative MTX dose of 1.0– 1.5 g and/or 3.5– 4.0 g. Time-to-event analysis was performed to determine the cumulative incidence, incidence rate, and factors potentially affecting the occurrence of hepatic fibrosis.Results: Of the 160 patients, 32 (20%) were treated with MTX-ACI, and 128 (80%) with MTX alone. Four patients (12.5%) in MTX-ACI group and 21 (16.4%) in MTX group developed hepatic fibrosis (p = 0.59). There was no statistically significant difference in cumulative incidence (16% in MTX-ACI vs 17% in MTX, p = 0.89) and incidence rate (37 cases per 1000 person-year in MTX-ACI vs 23 cases per 1000 person-year in MTX; hazard ratio [HR] = 1.07; p = 0.90) of hepatic fibrosis between the two groups. Diabetes and obesity were identified as significant factors associated with hepatic fibrosis (adjusted HR = 2.40, 95% confidence interval [CI]: 1.05– 5.51; p = 0.04 and adjusted HR = 3.28, 95% CI: 1.18– 9.16; p = 0.02, respectively) regardless of the cumulative MTX dose.Conclusion: The incidence of hepatic fibrosis in a real-life clinical situation, determined by transient elastography in patients with psoriasis receiving MTX-ACI, was not increased compared to those receiving MTX monotherapy. Type 2 diabetes mellitus and obesity were identified as risk factors of hepatic fibrosis; hence, patients with these factors receiving long-term MTX therapy should be regularly monitored for this particular event.Keywords: cirrhosis, combination therapy, drug, liver fibrosis, liver injury, non-alcoholic steatohepatitis